Warsztat dziennikarski Henryka Sienkiewicza – prolegomena - Pietrzak, Magdalena (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
Henryk Sienkiewicz is not only a well-known Polish writer appreciated for his mastery of language but also a journalist – reviewer, reporter and columnist of Warsaw newspapers of the second half of the 19th century. The paper is devoted to the most important features of Sienkiewicz’s journalistic workshop: skilful use of informal Polish with its phraseological and idiomatic vocabulary and aphorisms. Sienkiewicz, also known by the pseudonym „Litwos”, masterly used syntactic means: for creation and gradual increase of tension, for using rhythm in statements and for exposing those meanings that cannot be expressed only by words. Rich syntactic constructions based on parallel structures emphasized with anaphora or contrast and frequent use of enumeration are his favorite ways of building sentences. The importance of contextual background of Henryk Sienkiewicz’s workshop implied by his upbringing, education and interests is also stressed in this paper.